Helminths of the sand lizard, Lacerta agilis (Reptilia, Lacertidae), in the Palaearctic: faunal diversity and spatial patterns of variation in the composition and structure of component communities - Sharpilo, V.P.; Biserkov, V.; Kostadinova, A.; Behnke, J.M.; Kuzmin, Y.I. (Cambridge University Press, 2001)
We studied variation in the structure of component communities of helminths in sand lizards, Lacerta agilis, from 30 localities in the Ukraine and Bulgaria. Thirty-five separate samples of lizards, with a total of 661 completely censused infracommunities, yielded 30 helminth species (4 cestodes, 10 trematodes, 3 acanthocephalans and 13 nematodes). In its range within the Ukraine, L. agilis serves as the final host for 13 species of which only 3 (S. lacertae, S. hoffmanni and P. molini) can be considered as lizard specialists. A characteristic feature of these helminth component communities was thelarge proportion of heteroxeneous helminth species for which L. agilis serves as paratenic host. Sand lizards in the meadow steppeland zone were primarily parasitized by larval helminths that represented a major proportion of the total number of all worms recovered while those sampled in the grassland}forest transition zone were characterized by substantially higher proportions of adult helminths using lizards as final hosts. However, L. agilis was parasitized by a much higher proportion of lizard specialists in the `typical ' habitats of the meadow steppeland zone as opposed to those located in `marginal' habitats in the grassland/forest transition zone, where helminths were shared to a greater extent with amphibian hosts.